Promotion of Regular Oesophageal Motility to Prevent Regurgitation and Enhance Nutrition Intake in Long-Stay ICU Patients. A Multicenter, Phase II, Sham-Controlled, Randomized Trial: The PROPEL Study. Issue 3 (March 2020) - Heyland, Daren K.; Marquis, Francois; Lamontagne, Francois; Albert, Martin; Turgeon, Alexis F.; Khwaja, Kosar A.; Garland, Allan; Hall, Richard; Chapman, Martin G.; Kutsiogannis, Demetrios J.; Martin, Claudio; Sessler, Daniel I.; et al.
Abstract : Objectives: To evaluate the effect of esophageal stimulation on nutritional adequacy in critically ill patients at risk for enteral feeding intolerance. Design: A multicenter randomized sham-controlled clinical trial. Setting: Twelve ICUs in Canada. Patients: We included mechanically ventilated ICU patients who were given moderate-to-high doses of opioids and expected to remain alive and ventilated for an additional 48 hours and who were receiving enteral nutrition or expected to start imminently. Interventions: Patients were randomly assigned 1:1 to esophageal stimulation via an esophageal stimulating catheter (E-Motion Tube; E-Motion Medical, Tel Aviv, Israel) or sham treatment. All patients were fed via these catheters using a standardized feeding protocol. Measurements and Main Results: The co-primary outcomes were proportion of caloric and protein prescription received enterally over the initial 7 days following randomization. Among 159 patients randomized, the modified intention-to-treat analysis included 155 patients: 73 patients in the active treatment group and 82 in the sham treatment group. Over the 7-day study period, the percent of prescribed caloric intake (± SE) received by the enteral route was 64% ± 2 in the active group and 65% ± 2 in sham patients for calories (difference, –1; 95% CI, –8 to 6; p = 0.74). For protein, it was 57% ± 3 in the active group and 60% ± 3 in the sham group (difference, –3; 95% CI, –10 to 3; p = 0.30). Compared to the sham group, there were more serious adverse events reported in the active treatment group (13 vs 6; p = 0.053). Clinically important arrhythmias were detected by Holter monitoring in 36 out of 70 (51%) in the active group versus 22 out of 76 (29%) in the sham group ( p = 0.006). Conclusions: Esophageal stimulation via a special feeding catheter did not improve nutritional adequacy and was associated with increase risk of harm in critically ill patients. Abstract : Supplemental Digital Content is available in the text.